Cardiometabolic Risk Variables in Preadolescent Children: A Factor Analysis. Issue 10 (11th October 2017) - Stoner, Lee; Weatherall, Mark; Skidmore, Paula; Castro, Nicholas; Lark, Sally; Faulkner, James; Williams, Michelle A.
Abstract : Background: Atherosclerosis begins during preadolescence and is occurring at an accelerated rate. This acceleration has been linked to poor lifestyle behaviors and subsequent cardiometabolic complications. Although the clustering of cardiometabolic risk factors has been recognized for over 2 decades, previous studies in children have predominantly examined the relationships between atherosclerosis and individual cardiometabolic risk factors or have grouped together preadolescent and adolescent children. Further, no known studies have included glycated hemoglobin or central hemodynamic measures such as central systolic blood pressure and augmentation index. Methods and Results: Principal component analysis was performed on a cross‐sectional sample of 392 children (aged 9.5 years, 50% girls) from 3 representative sample sites across New Zealand. Four factors explained 60% of the variance in the measured variables. In order of variance explained, the factors were: blood pressure (central systolic blood pressure and peripheral systolic and diastolic blood pressure), adiposity (waist circumference, body mass index, and glycated hemoglobin), lipids (total cholesterol, low‐density lipoprotein cholesterol, and high‐density lipoprotein cholesterol), and vascular (augmentation index, heart rate, and fasting blood glucose). Conclusions: In accordance with previous findings in adults and adolescents, one common factor is unlikely to define cardiometabolic health in preadolescent children. Each of the factors, except vascular, which was predominantly explained by augmentation index, are in agreement with previous findings in adolescents. An additional novel finding was that glycated hemoglobin and fasting blood glucose loaded onto different factors, supporting previous work suggesting that fasting blood glucose indicates short‐term glycemic control, whereas glycated hemoglobin reflects chronic glycemic control. Clinical Trial Registration: URL:www.anzctr.org.au/ . ID: ACTRN12614000433606.